PENGARUH EFEKTIFITAS KOMITE AUDIT TERHADAP FINANCIAL DISTRESS - Rahmawati, Evi; Herlambang, Prasetya (Jurnal Reviu Akuntansi dan Keuangan)
This study examines the effect of the size of the audit committee, the independence of the  audit committee, frequency of meetings; financial literacy; liquidity; leverage and profitability towards company’s financial distress. This study uses manufacturing companies listed on the Indonesia Stock Exchange (IDX), Malaysia Stock Exchange (KLSE) and Singapore Stock Exchange (SGX) period 2014-2015. The number of manufacturing companies that is used in this study comprises of 124 Indonesian companies; 138 Malaysian companies and 98 Singapore companies. This study also analyzes the effect of company’s financial distress towards the possibility of fraud. The results of this study shows that there is a significant positive effect of leverage towards financial distress in Indonesia and in Singapore. There are differences in factors affecting financial distress in Indonesia and Malaysia. There are differences in factors affecting financial distress in Indonesia with Singapore. As for the size of the audit committee, the independence of audit committees, frequency of meetings, financial knowledge, liquidity, and profitability do not affect significantly towards company’s financial distress.